Thermoreversible in situ gel for subgingival delivery of simvastatin for treatment of periodontal disease - Rajendran, Swaminathan (Int J Pharm Investig, 2017)
OBJECTIVE: The aim of this in vitro study was to formulate an in situ thermoreversible injectable gel with poloxamer (PM) and methylcellulose (MC) to deliver simvastatin (SMV) in a controlled manner. SUBJECTS AND METHODS: Preformulation studies (Fourier transform infrared and differential scanning calorimetry) to assess the interaction between SMV and MC and PM were performed before gel formulation. Keeping the concentration of SMV at 2.2%, the concentration of PM and MC was altered to formulate in situ thermosensitive gel at 37°C. Rheological studies were carried to analyze the physical property of the various formulations. Drug release profile and stability studies were done for the selected formulation. The in vitro drug release profile was carried out for using open end tube method and ultraviolet spectroscopy. RESULTS: The preformulation studies showed that there is no interaction between the polymer and drug based on the rheological studies of different formulation, the formulation. F8 gels at 37°C and attains a viscosity of 4150 cps. CONCLUSIONS: PM 25% and MC 5% formed an ideal thermosensitive injectable gel at 37°C for subgingival delivery of SMV and also show controlled drug release for the period of 10 days in vitro.